2016
DOI: 10.1016/j.jvs.2016.04.036
|View full text |Cite
|
Sign up to set email alerts
|

Results of common femoral artery thromboendarterectomy evaluation of a traditional surgical management in the endovascular era

Abstract: Open surgery for common femoral artery stenosis is safe and effective in the long-term. Endovascular therapy will need to compete with these excellent results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 14 publications
3
42
0
Order By: Relevance
“…Cumulatively, wound haematoma occurred in 24 of 269 procedures (5·5 (95 per cent c.i. 0·2 to 17·2) per cent; 4 studies), similar to 35 of 1154 in the endarterectomy group (3·9 (1·7 to 6·9) per cent; 7 studies). No wound infection or lymph leak was reported in the endovascular group.…”
Section: Resultsmentioning
confidence: 78%
See 4 more Smart Citations
“…Cumulatively, wound haematoma occurred in 24 of 269 procedures (5·5 (95 per cent c.i. 0·2 to 17·2) per cent; 4 studies), similar to 35 of 1154 in the endarterectomy group (3·9 (1·7 to 6·9) per cent; 7 studies). No wound infection or lymph leak was reported in the endovascular group.…”
Section: Resultsmentioning
confidence: 78%
“…Only ten studies collected data prospectively, of which five reported endovascular intervention and five reported CFE. Less than half of the studies (11 of 28) had a sample size of greater than 100 and follow‐up of 1 year or more, of which four were in the endovascular group and seven were in the CFE group ( Table S6 , supporting information).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations